Utility of ACMG classification to support interpretation of molecular genetic test results in patients with factor VII deficiency - Alesci, Rosa Sonja; Hecking, Carola; Racké, Benjamin; Janssen, Detlev; Dempfle, Carl-Erik (Frontiers in Medicine, 2023)
The American College of Medical Genetics and Genomics (ACMG) and the Association for Molecular Pathology (AMP) have introduced an internationally shared framework for variant classification in genetic disorders. FVII deficiency is a rare inherited autosomal recessive bleeding disorder with sparse data concerning ACMG classification.To develop an approach which may improve the utility of molecular genetic test results, 129 patients with FVII deficiency were retrospectively assigned to six subgroups for exploratory analysis: F7 gene wildtype (group 1), ACMG 1 (benign variant) or ACMG 2 (likely benign variant), only (group 2), ACMG 3 (variant of uncertain significance) ± ACMG 1-2 heterozygous or not classified variant (group 3), ACMG 4 (likely pathogenic variant), or ACMG 5 (pathogenic variant) single heterozygous ± ACMG 1-3 single heterozygous (group 4), ACMG 4-5 homozygous or ≥2 ACMG 4-5 heterozygous or ≥1 ACMG 4-5 heterozygous plus either ACMG 1 c.1238G>A modifying variant homozygous or ≥2 ACMG 1-3 (group 5), FVII deficiency and another bleeding disorder (group 6). Results: Eleven of 31 patients. (35.5%) in group 5 had abnormal ISTH-BS (n=7) and/or history of substitution with recombinant factor VIIa (n=5) versus 4 of 80 patients (5.0%, n=1 abnormal ISTH-BS, n=3 substitution) in groups 1 (n=2/22), 2 (n=1/29), 3 (n=0/9), and 4 (n=1/20). Four of 18 patients (22.2%) with FVII deficiency and another bleeding disorder (group 6) had an abnormal ISTH-BS (n=2) and/or history of substitution with recombinant factor VIIa (n=3) Conclusions: Patients with a homozygous ACMG 4-5 variant or with specific combinations of heterozygous ACMG 4-5 ± ACMG 1-3 variants exhibited a high-risk bleeding phenotype in contrast to the remaining patients without another bleeding disorder. This result may serve as a basis to develop a genotype/phenotype prediction model in future studies.